PEMBAHARUAN HUKUM ISLAM DALAM PEMBERDAYAAN WAKAF PRODUKTIF TERHADAP KESEJAHTERAAN MASYARAKAT - samud samud (Mahkamah : Jurnal Kajian Hukum Islam, 2019)
In this time of economic growth which is quite alarming, actually the role of waqf in addition to other instruments, the benefits can be felt to improve the standard of living of the community, especially in the economic field, if the waqf is managed properly. The allocation of waqf in Indonesia which does not lead to the economic empowerment of the people and tends to be only for the interests of special worship activities is more because it is influenced by the limitations of Muslim understanding of waqf, both in the endowments, endowments and endowments. In general Indonesian Muslims understand that the allocation of waqf is only limited to the interests of worship and things that are commonly implemented in Indonesia such as for mosques, prayer rooms, tombs, and so on. Specifically in Indonesia until now the potential of waqf as a means of doing good for the interests of the community has not been maximally utilized, moreover clothing as an object of waqf has never been done nationally and internationally. Even though the essence of an endowment object is to have economic values that can be utilized and utilized to the fullest for the sake of empowering the interests of Muslim